(untitled)
tc Hkh m".kdfVca/kh; pØokr vkrk gS rc Hkkjr vkSj blds fudVorhZ ks=ksa esa rwQkuh leqnzh rjaxksa dh vkinkvksa ds dkj.k tku vkSj eky dh Hkkjh gkfu] rVh; <k¡pksa dh kfr vkSj —f"k dks gkfu igq¡prh gSA uoEcj 1970 esa caxykns’k ¼igys iwohZ ikfdLrku½ esa vk, ,d vR;ar iapaM pØokr dh otg ls yxHkx 3]00]000 yksxksa dh tkus xbZaA uoEcj 1977 esa vkU/kz esa vk, pØokr us Hkkjr ds iwohZ rV dks rgl ugl dj fn;k ftlesa yxHkx 10]000 yksxksa dh tkus xbZaA vDrwcj 1999 esa Hkkjr ds mM+hlk ds rV ij ,d izpaM pØokrh rwQku vk;k ftlls ml ks= esa laifRr dh vR;kf/kd gkfu gksus ds vfrfjDr 15]000 ls Hkh vf/kd yksxksa dh tkus xbZaA gky gh esa ebZ 2008 esa vk, pØokr uxhZl ls E;kaekj esa yxHk.k 1]40]000 yksxksa dh tkusa xbZa vkSj laifRr dk vR;f/kd ek=k esa uqdlku gqvkA ;s fo’o dh lcls cM+h ekuoh; vkink;sa eq[;r% m".kdfVca/kh; pØokrksa ls lac) gaS o leqnzh rwQkuh rjaxksa ls izR;k:i ls tqMh gSA vr% ml ks= esa lafkIr iwokZuqeku vkSj leqnzh rwQkuh rjaxksa dh iwoZ psrkouh nsus dk izko/kku ml ks= ds fgr esa gksrk gSA bl ’kks/k i= dk eq[; mÌs’; caxky dh [kkM+h vkSj vjc lkxj esa mBus okyh leqnzh rwQkuh rjaxksa dk iwokZuqeku djus ds fy, gky gh esa fodflr fd, x, ekWMyksa dks izdk’k esa ykuk gSA bl ’kks/k&i= esa o"kZ 2008 ls 2011 ds nkSjku caxky dh [kkM+h esa cus izpaM pØokrksa ls tqM+h leqnzh rjaxksa dk iwokZuqeku yxkus@vuqdj.k djus esa fun’kZ ds fu"iknu dk Hkh mYys[k fd;k x;k gSA Storm surge disasters cause heavy loss of life and property, damage to the coastal structures and the losses of agriculture in India and its neighborhood whenever a tropical cyclone approaches. About 3,00,000 lives were lost in one of the most severe cyclone that hit Bangladesh (then East Pakistan) in November 1970. The Andhra Cyclone devastated the eastern coast of India, killing about 10,000 persons in November 1977. Orissa coast of India was struck by a severe cyclonic storm in October 1999, killing more than 15000 people besides enormous loss to the property in the region. More recently the Nargis cyclone of May 2008 killed about 1,40,000 people in Myanmar as well as caused enormous property damage. These and most of the world’s greatest human disasters associated with the tropical cyclones have been directly attributed to storm surges. Thus, provision of precise prediction and warning of storm surges is of great interest in the region. The main objective of the present paper is to highlight the recent developments in storm surge prediction model for the Bay of Bengal and the Arabian Sea. Paper also describes the performance of the model in forecasting/simulating the surges associated with severe cyclones formed in the Bay of Bengal during 2008 to 2011. , number=1, journal=MAUSAM, year=2013, month=Jan., pages=193–202